Characterization of Viloxazine Effects on Cortical Serotonin Neurotransmission at Doses Relevant for ADHD Treatment. (April 2023) - Garcia-Olivares, Jennie; Yegla, Brittney; Earnest, Jami; Maletic, Vladimir; Yu, ChungPing
Abstract: Introduction: Most ADHD treatments are thought to be effective due to augmentation of dopamine (DA) and norepinephrine (NE). Our prior preclinical studies found that the ADHD treatment, viloxazine, may augment serotonin (5-HT) in addition to NE and DA; however, it was unclear if these effects occurred at clinically relevant concentrations. To further understand these potential 5-HT effects, we conducted a series of experiments with two objectives: 1) Can we confirm and better elucidate the previously observed serotonergic effects of viloxazine and determine if they occur at clinically relevant concentrations? 2) Are these effects observed in species with close physiology to humans? Methods: Objective 1: The affinity of viloxazine for human isoforms of 5-HT2A, 5-HT2B, 5-HT2C, and 5-HT7 receptors was assessed via cell-based binding assays. Viloxazine agonism of 5-HT2C and antagonism at 5-HT7 was elucidated with IP1, Ca 2+, β-arrestin, internalization, and cAMP assays in cells expressing human receptor isoforms. A microdialysis study was conducted in rats to determine the relationship between viloxazine concentrations in the interstitial fluid (ISF) and changes in NE, DA, 5-HT, and their metabolite concentrations in the prefrontal cortex (PFC). Objective 2: A PET imaging study using a 5-HT2A/2C radioligand agonist, [ 11 C]CIMBI-36, is being conducted in non-human primates (NHPs) to evaluate if viloxazine binds these receptors and/or increases 5-HT release. Animal research was approved by animal care and use committees. Animals were cared for according to international standards. Results: Objective 1: Cell-based assays to measure viloxazine affinity for NET, 5-HT2B, 5-HT2C, and 5-HT7 found Ki values of 0.14, 0.65, 0.84, 1.90 μM respectively. These values were lower than therapeutically relevant rat ISF concentrations (3.5 ± 1.6 μM) approximating pediatric ADHD patients unbound plasma concentrations (2.1-3.3 μM), indicating receptor recruitment. Binding affinity and functional activity assays found viloxazine had negligible activity for 5-HT2A and SERT at therapeutic concentrations. Viloxazine 5-HT2C agonism activated Gq -protein signaling (EC50 =1.6 μM, Ca 2+ assay), but not β-arrestin or internalization pathways (EC50 values >150 μM). Viloxazine 5-HT7 antagonism decreased Gs -protein signaling (IC50 =6.7 μM). The microdialysis study found that at therapeutically relevant ISF concentrations, 5-HT levels were significantly increased over baseline; no changes were seen in the 5-HIAA metabolite, indicating 5-HT increase is not due to 5-HT reuptake inhibition. Objective 2: PET imaging studies are ongoing. Conclusions: To date, our experiments to further elucidate the potential 5-HT effects of viloxazine have shown that the previously observed effects of viloxazine on 5-HT receptors and its augmentation of 5-HT in rat PFC occur at clinically relevant concentrations. Further exploration is needed to ascertain if these effects occur in NHPs and are relevant to ADHD. Funding: Supernus Pharmaceuticals, Inc.